A Swelling in the Mouth in a Chronic Hemodialysis Patient - Arnaud Devresse; Alexandros Raptis; Anne-Sophie Claes; Laura Labriola (Case Reports in Nephrology)
Oral manifestations of severe secondary hyperparathyroidism include maxillary and mandibular deformities, brown tumors, dental abnormalities, and metastatic calcification of soft tissues. We report on a chronic hemodialysis (HD) woman with severe, uncontrolled secondary hyperparathyroidism and a painful, nontender mass in the floor of her mouth. The most likely clinical diagnosis was a bone tumoral lesion of the oral cavity, secondary to renal osteodystrophy. Unexpectedly, pathological examination showed characteristic features of ossifying fibroma (OF) of the jaw, a rare, benign fibroosseous lesion characterized by the replacement of normal bone by collagen and fibroblasts containing varying amounts of mineralized substance. The occurrence of an OF in chronic HD patients is exceptional. Differential diagnosis must be made with bone tumoral lesions secondary to renal osteodystrophy. Surgical removal is the treatment of choice. The pathogenesis of OF in the setting of secondary hyperparathyroidism remains unknown. Parathyroidectomy may not be necessary to avoid OF recurrence after surgical removal.